2017
DOI: 10.1137/15m1032910
|View full text |Cite
|
Sign up to set email alerts
|

Bounded-Degree Spanning Trees in Randomly Perturbed Graphs

Abstract: We show that for any fixed dense graph G and bounded-degree tree T on the same number of vertices, a modest random perturbation of G will typically contain a copy of T . This combines the viewpoints of the well-studied problems of embedding trees into fixed dense graphs and into random graphs, and extends a sizeable body of existing research on randomly perturbed graphs. Specifically, we show that there is c = c(α, ∆) such that if G is an n-vertex graph with minimum degree at least αn, and T is an n-vertex tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 19 publications
2
53
0
1
Order By: Relevance
“…Krivelevich, Kwan and Sudakov [16] studied the corresponding problem for the containment of bounded degree trees and showed that p = ω(1/n) is sufficient in this case. For p = ω(1/n) it is already possible to find any almost spanning bounded degree tree in G(n, p) [4].…”
Section: Randomly Perturbed Graphsmentioning
confidence: 99%
“…Krivelevich, Kwan and Sudakov [16] studied the corresponding problem for the containment of bounded degree trees and showed that p = ω(1/n) is sufficient in this case. For p = ω(1/n) it is already possible to find any almost spanning bounded degree tree in G(n, p) [4].…”
Section: Randomly Perturbed Graphsmentioning
confidence: 99%
“…Krivelevich et al [28] studied the corresponding problem for the containment of spanning trees of maximum degree in G α ∪ G(n, p). For p = c(ε, )/n, it is already possible to find any almost spanning bounded degree tree on (1 − ε)n vertices in G(n, p) [4].…”
Section: Formentioning
confidence: 99%
“…Here, it is worth mentioning that in the Erdős-Rényi random graph, G n m ( , ), the threshold for Hamiltonicity is n nn (log + log log ) . G H m , has since been studied in a number of other contexts (see, eg, [1,3,9,10,13] (1)) ] color a typical graph of minimum degree δn, then w.h.p. the resultant graph will contain a rainbow-Hamilton cycle.…”
Section: H M R mentioning
confidence: 99%